Horseweed (Marestail) Resistance - Lester, Alec; Rains, Larry; Dille, J. Anita (My University, 2018)
Horseweed has documented resistance to EPSPS inhibitors, PSII inhibitors, ALS inhibitors, and PSI inhibitor (Heap, 2018). Glyphosate resistant horseweed moves the herbicide into a vacuole preventing the herbicide from damaging the plant (Ge, 2010). The objective of the this experiment was to determine if nine different horseweed populations were resistant or not to six different herbicide. Experimental design was a randomized complete block with six herbicides, nine locations, and five replications. Heights were recorded for each population before spraying. Each herbicide was sprayed on October 5, 2018, and rates were paraquat (840 g ai/ha), glyphosate (1260 g ae/ha), glufosinate (738 g ai/ha), Atrazine (560 g ai/ha), chlorimuron (13.1 g ai/ha), and dicamba (560 g ai/ha). Horseweed showed the most resistance to atrazine and glyphosate across all locations, and paraquat in some locations. No herbicide had total control fourteen days after spraying. Dicamba had the greatest control of horseweed across all nine locations. Resistance was difficult to identify because horseweed plants were too mature to effectively be control.
Keywords: Fall 2018